(untitled) (E Global Congress, 2026)
The article analyzes regional mechanisms and prospects for increasing the efficiency of the location of industrial enterprises based on a systematic approach. As a key component of the regional economy, the territorial location of industrial enterprises accelerates economic growth through the rational use of production resources, optimization of transport and logistics infrastructure, and strengthening inter-sectoral integration. The study examines the factors affecting the efficiency of location - the distribution of natural resources, labor market potential, infrastructure development, investment environment, and the activity of innovation clusters - in connection with regional competitiveness.